Bacteremia in a Renal Transplant Recipient - Syed M. H. Zaidi MBBS; Ambika Eranki MD, MPH (SAGE Publishing, 2019)
A middle-aged man presented with fever and shortness of breath. He had significant history of congestive heart disease and received deceased donor renal transplant 2 years prior to presentation. He was febrile and found to have sepsis. His initial blood cultures grew Streptococcus canis. Streptococcus canis causes rare infection in humans, and this is most likely the first case in the renal transplant population.